Iron Storage in Friedreich's Ataxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
To test the hypothesis that iron is increased in the cerebellum of patients with Friedreich's ataxia (FA), a multigradient echo magnetic resonance sequence for the three-dimensional imaging of brain iron-induced contrast was used in 12 patients and 23 normal subjects examined at the National Institutes of Health, Bethesda, MD.